2017
DOI: 10.1080/14790718.2017.1411916
|View full text |Cite
|
Sign up to set email alerts
|

The ideal multilingual self: validity, influences on motivation, and role in a multilingual education

Abstract: L2 motivation research has a longstanding monolingual bias. Recently, however, the motivational systems of a multilingual's different languages have been conceptualized as constituting a multilingual motivational system, and it has been suggested that interactions between the ideal Lx self and the ideal Ly self can lead to the emergence of an ideal multilingual self. While the notion of an ideal multilingual self chimes with research on multilinguals' identity experiences, it has not been investigated empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 45 publications
0
44
1
6
Order By: Relevance
“…In addition, we investigated differences between the two groups for positive and negative affect that we measured at the end of each lesson. We adapted questionnaire items for measuring the students’ ideal self aspirations from Henry and Thorsen () and asked whether the students could imagine speaking either English in the future (English ideal self aspirations) or additional languages besides English and their own family languages (plurilingual ideal self aspirations). We wrote the questions in simple sentences and used smiley faces to facilitate comprehension.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we investigated differences between the two groups for positive and negative affect that we measured at the end of each lesson. We adapted questionnaire items for measuring the students’ ideal self aspirations from Henry and Thorsen () and asked whether the students could imagine speaking either English in the future (English ideal self aspirations) or additional languages besides English and their own family languages (plurilingual ideal self aspirations). We wrote the questions in simple sentences and used smiley faces to facilitate comprehension.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, Q6's instrumental concerns shifted to a stronger cultural interest when she co-adapted with the positive Spanish-learning context (see Excerpt 4). When the group sharing the motivational profile of Factor 1 finally arrived at an attractor state of the constitutive multilingual self at Time 3, their L2-English-specific ideal self and L3-Spanish-specific ideal self reached a dynamic equilibrium and coexisted harmoniously within the multilingual self system (Henry, 2017;Henry & Thorsen, 2018). Furthermore, direct and intensive contact with the target L2 community helps to sharpen the image of a competent target-language user and brings to the fore the integrative aspect of Q11's and Q14's multilingual selves.…”
Section: Holistic Dynamic and Relational Multilingual Motivationmentioning
confidence: 99%
“…The ideal multilingual self was conceptualized as emergent properties of the interactions between language‐specific ideal selves, and assumed to be important in helping to reconcile the potential conflicts or competition between these language‐specific ideal selves. In a follow‐up study, Henry & Thorsen (2018) found that the ideal L2 self and the ideal multilingual self were two conceptually distinct constructs, but the ideal multilingual self did not have a direct effect on the intended efforts to learn the chosen LOTE. They argued that the ideal multilingual self should be considered at a higher, more abstract level above the language‐specific ideal selves.…”
Section: A Holistic Dynamic and Relational View Of Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, from a pedagogical point of view there is as yet very little attempt to relate the kinds of identity-focused aims and activities discussed above to existing mainstream foreign language classroom pedagogy. Nor, more importantly, has there been research measuring the effects of a systematic pedagogical intervention aimed at fostering multilingual identity within the context of classroom-based additional language learning, something advocated by Henry and Thorsen (2017) in relation to development of the multilingual ideal self. The following section of this paper outlines what such an approach might look like.…”
Section: Multilingual/linguistic Identity Research In Educational Conmentioning
confidence: 99%